OPINI AUDIT GOING CONCERN SEBAGAI PEMODERASI PENGARUH PERTUMBUHAN PERUSAHAAN DAN PERGANTIAN MANAJEMEN PADA AUDITOR SWITCHING - Putri Alansari, I Gusti Ayu; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 15 No 2 (2016), 2016)
Auditor switching have a definition the alternation public accountant that carried out by an entity. There are two underlying reasons, lack of regulation of related parties (in this case is the decision of finance ministers) or the policy of entity concerned (voluntary). Obviously there is a fundamental cause the alternation of the public accountant or the firm voluntarily in an entity so this research aimed to analyze whether the going concern audit opinion can be a moderating influence firm growth and management changes on auditor switching. Entities at financial sector listed in Indonesia Stock Exchange (BEI) of 2010-2013 became the object of this research. Sampling technique based on criteria and obtained 84 observations. Researcher used analysis techniques such as logistic regression. The results is firm growth in a positive and significant influence on auditor switching. However, management changes does not affect on auditor switching. Going concern audit opinion was able to significantly weaken the influence of the firm growth on auditor switching, but are not able to affect management changes on auditor switching.
Keywords: firm growth, management changes, going concern audit opinion, auditor switching